1998
DOI: 10.1111/1467-839x.00011
|View full text |Cite
|
Sign up to set email alerts
|

How Effective are Different Accounts of Harm‐doing in Softening Victims’ Reactions? A Scenario Investigation of the Effects of Severity, Relationship, and Culture

Abstract: In order to examine the effects of different types of accounts in terms of the victims' reactions, we presented 193 American and 186 Japanese participants with scenarios in which an actor unintentionally harmed someone and then gave one of five different accounts. We asked the participants to estimate how the victim would react (emotional alleviation, impression improvement, or forgiveness) to these accounts. The participants rated that the victims would make more positive reactions to the mitigative accounts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 14 publications
3
29
0
Order By: Relevance
“…Koreans also reported a greater intention to use apologies than did Americans (d = 1.05, large effect). Whereas Fukuno and Ohbuchi (1998) found that individualists and collectivists might find apologies equally costly and effective, Takaku (2000) and Sugimoto (1997) found Americans less willing to apologize than were Japanese, and Park et al (2005) found Americans less willing to apologize than were Koreans.…”
Section: Collectivism and Talking About Transgressionsmentioning
confidence: 96%
See 2 more Smart Citations
“…Koreans also reported a greater intention to use apologies than did Americans (d = 1.05, large effect). Whereas Fukuno and Ohbuchi (1998) found that individualists and collectivists might find apologies equally costly and effective, Takaku (2000) and Sugimoto (1997) found Americans less willing to apologize than were Japanese, and Park et al (2005) found Americans less willing to apologize than were Koreans.…”
Section: Collectivism and Talking About Transgressionsmentioning
confidence: 96%
“…Accounts for negative behavior can deny responsibility or justify the behavior (often by blaming the victim) or can mitigate tension by naming excusing circumstances or confessing responsibility (Takaku, 2000). Four studies (Fukuno & Ohbuchi, 1998;Park, Lee, & Song, 2005;Sugimoto, 1997;Takaku, 2000) examined cultural differences in account styles (see Table 2). …”
Section: Collectivism and Talking About Transgressionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eloise K. Thomas and Geoffrey W. Sutton 309 Additional research has focused on apology (Sugimoto, 1998) and people's responses to apology (Fukuno & Ohbuchi, 1998;Ohbuchi & Sato, 2001), including forgiveness (Azar, Mullet, & Vinsonneau, 1999). Some have questioned whether an apology is a necessary precursor to forgiveness (e.g., Finch, 2006).…”
Section: Forgiveness Apology and Restitutionmentioning
confidence: 99%
“…Some have questioned whether an apology is a necessary precursor to forgiveness (e.g., Finch, 2006). Others have looked at cultural differences in response to apology or at apology in cultures other than the United States (Fukuno & Ohbuchi, 1998;Sugimoto, 1998). Still others have studied the use of apology in a legal or mediation setting (Cohen, 1999;Regehr & Gutheil, 2002;Rehm & Beatty, 1996;Schneider, 2000;Worthington, 2000).…”
Section: Forgiveness Apology and Restitutionmentioning
confidence: 99%